Methodological issues of cultural evaluation in the context of political prosumption - Savelieva, Elena N. (Questions of expertise in culture, arts and design, 6-7 June 2019, Yekaterinburg, Russia)
The article is devoted to the search for theoretical and methodological foundations of cultural evaluation as a new area of expert activity. There are two new elements in this study. First, while studying online visual images, a number of artistic methods are identified that can be used as criteria in the analysis and evaluation of extremist content materials. Secondly, the analysis is conducted taking into account the characteristics of the digital environment, which ensures the relevance of these criteria to modern social and cultural reality. The article shows that political prosumption creates favourable conditions for the dissemination of conflict-generating and extremist content. It is possible to counteract this destructive tendency by appealing to universally recognized values, such as the victory in the Great Patriotic War in the context of Russian history. This article suggests that civic identity should be used as the foundation of expert analysis, based on a non-alternative recognition of the heroic role of the Soviet people and rejection of Nazism ideology. In the process, the methods of Nazi ideology propaganda are revealed via examples centering on the destruction of the foundations of civic identity